2021
DOI: 10.15446/dyna.v88n217.93354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential waste heat recovery from a stenter in a textile plant

Abstract: The textile sector, an important economic driving force in Antioquia, Colombia, uses great quantities of thermal energy mainly produced by coal combustion, which holds enormous potential for recovery. One of the most common processes in a textile plant is heat setting, which uses a significant amount of thermal energy to adjust the properties of fabrics, such as shrinking, stiffness, pull strength, width, and stretching. In this study, we calculate the mass and energy balances of a stenter and propose a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Cacua et al proposed a system for recovering usable energy from the exhaust gas discharge of the stentering process, and they calculated the mass and energy balances for each heat exchanger to determine the optimal heat exchanger that can achieve the maximum amount of recovered heat energy. 9 The calculation results indicated that up to 30.1% energy savings can be achieved using a thermalsyphon heat exchanger. Pulat et al used a wasteheat recovery system to recover waste heat generated in the dyeing process, and they calculated the energy consumption by conducting a thermodynamic analysis.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Cacua et al proposed a system for recovering usable energy from the exhaust gas discharge of the stentering process, and they calculated the mass and energy balances for each heat exchanger to determine the optimal heat exchanger that can achieve the maximum amount of recovered heat energy. 9 The calculation results indicated that up to 30.1% energy savings can be achieved using a thermalsyphon heat exchanger. Pulat et al used a wasteheat recovery system to recover waste heat generated in the dyeing process, and they calculated the energy consumption by conducting a thermodynamic analysis.…”
Section: Literature Reviewmentioning
confidence: 98%
“…As a result, the total energy consumption of stentering process is 918.65 kW, and about 800 kW of waste heat is able to recover, which reduces total amount of energy consumption about 30.1%. 9 Rossane et al developed the heat and mass transfer in a porous media model to simulate stenetring process and investigated the influence of ambient conditions on the performance of the stentering process. 12 As a result of simulation, the natural gas consumption increased by 5.3% when the simulation represented the operation of the stenter in cold air and that recovery of exhaust air saved 19% to 64% of natural gas.…”
Section: Literature Reviewmentioning
confidence: 99%